Thermal comfort in free running and mechanically conditioned learning facilities / Khairul Nazli Razali and Zalida Salleh - Razali, Khairul Nazli; Salleh, Zalida (2018)
Alhough the standard for acceptable indoor conditions for comfort cooling in non-residential buildings has been established, it is still arguable whether the standard is able to satisfy every condition since thermal comfort may be influenced by various factors. Hence, this study aims to determine the suitable temperature that will maximize the thermal comfort at a given specific location, namely the learning facilities situated at Faculty of Architecture, Planning and Surveying (FSPU), Universiti Teknologi Mara, Shah Alam. The main objective of this study is to compare the comfort temperature obtained using two different methods namely Predicted Mean Vote, which is considered as an objective measurement, and Actual Mean Vote, which is considered as a subjective measurement. Physical parameters at four different learning facilities were taken. Three of the learning facilities are categorised as mechanically conditioned building and one is categorised as a free running building. A total of 109 students were surveyed. Comfort temperature for free running building in FSPU is found to be 27°C according to PMV and 27.10°C according to AMV. Whereas, the comfort temperature for mechanically conditioned building is found to be 24.10°C in accordance to PMV and 26.90°C in accordance to AMV.